Urban Park Planning for Sustainability: Resident Insights from China’s Major Cities - Biao He; Siyu Wang; Qian Xiong; Zheng Zhao; Yilei Hou (Land)
Urban parks are pivotal in the sustainable development of urban ecosystems, significantly enhancing the ecological environment and residents’ quality of life. To scientifically improve urban park management and ensure long-term sustainability, this study aims to establish a framework for understanding and predicting residents’ spatial perceptions in urban parks. Overcoming the constraints of traditional empirical research, this study conducted a questionnaire survey involving 701 residents from Beijing Chaoyang Park, Shanghai Century Park, and Guangzhou Yuexiu Park from May to July 2024. By combining the semantic differential (SD) method, importance–performance analysis (IPA), and cognitive map methods, the study holistically assessed residents’ spatial perceptions and their variations in urban parks. The SD analysis highlighted perceptional differences in the three urban parks, revealing the needs for tailored planning considering personal characteristics and geographical location, which is essential for enhancing park services and overall satisfaction. Comparative analysis showed significant variations in the preferences in different resident groups, with Chaoyang Park facing a sense of deprivation due to weaker natural features, suggesting the critical role of natural elements in park design, while Century and Yuexiu Parks were highly valued for aligning park design with local needs and preferences. Cognitive maps reveal residents’ spatial perception of urban parks, particularly their significant differences in familiarity with the natural and social functions, artificial landscapes, and internal attractions of parks, which informs the integration of design elements that cater to varying preferences and foster a stronger sense of place. This study confirms the effectiveness of combining traditional methods with spatial perception analysis for quantitatively evaluating residents’ spatial perception, and provides useful references for the sustainable planning and management of urban parks.